Barriers to discontinuing antidepressants in patients with depressive and anxiety disorders: a review of the literature and clinical recommendations - Willemijn Scholten; Neeltje Batelaan; Anton Van Balkom (SAGE Publishing, 2020)
Use of antidepressants has recently increased, mainly caused by the increase of long-term users. Although evidence-based indications for long-term use are lacking, it is assumed that long-term use is unnecessary or undesirable in some patients. Perceived barriers to discontinuing antidepressants contribute to unnecessary or undesirable long-term use. Identifying barriers prior to, during and following discontinuation may enable strategies to overcome them. This narrative review summarises relevant qualitative and quantitative articles on perceived barriers to discontinuing antidepressants and provides recommendations for clinical practice. We can conclude that implications for clinical practice are diverse and the most important barriers experienced by patients and physicians include the fear of relapse or recurrence, insufficient evaluation and monitoring, withdrawal symptoms, and actual relapse or recurrence.